2006
DOI: 10.1258/135763306777889073
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic stakes in the development of telemedicine

Abstract: This brief article points out that more empirical knowledge is required about the diverse factors that influence the diffusion, implementation, outcomes and behaviours associated with the spread of information and communication technologies (ICT). This includes the domain of telemedicine and ICT-based outpatient care. A detailed understanding of these processes and the participants involved offers the potential to illuminate the multiplicity of inter-related issues with which medical practitioners and health-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Studies (Keddie & Jones, 2005;Lougheed, 2004) have shown that ICT use in medical practices has expanded from being a clinical tool to include business and practice management. Recent studies (Bonneville & Pare, 2006;Lievens & Jordanova, 2004) suggest that for any medical practice to remain viable, there must be parity between medical and business efficiency. Indeed, Kuruvilla et al (2004) suggest that ICT use in general practice centralises geographically dispersed resources, thus promoting flexibility and economies of scale, promotes efficiency, enhances quality of care and encourages partnerships between practitioners and between patients and practitioners.…”
Section: The Nature Of Ict Use In Medical Practicementioning
confidence: 99%
“…Studies (Keddie & Jones, 2005;Lougheed, 2004) have shown that ICT use in medical practices has expanded from being a clinical tool to include business and practice management. Recent studies (Bonneville & Pare, 2006;Lievens & Jordanova, 2004) suggest that for any medical practice to remain viable, there must be parity between medical and business efficiency. Indeed, Kuruvilla et al (2004) suggest that ICT use in general practice centralises geographically dispersed resources, thus promoting flexibility and economies of scale, promotes efficiency, enhances quality of care and encourages partnerships between practitioners and between patients and practitioners.…”
Section: The Nature Of Ict Use In Medical Practicementioning
confidence: 99%
“…At first glance these may appear to be at odds with one another, with clinical use aimed at quality and efficiency of medical care, and with business use aimed at profitability and budgetary concerns. However, recent studies (Bonneville & Pare, 2006;Lievens & Jordanova, 2004;Rahimi & Vimarlund, 2007) suggest that, for any medical or healthcare function to be truly viable, there must be a balance between medical and business efficiency. Indeed, Kuruvilla et al (2004) suggest that the use of ICTs in general practice not only centralises geographically dispersed resources, thus promoting flexibility and economies of scale, but also promotes efficiency, enhances quality of care and encourages partnerships both between practitioners as well as between patients and practitioners.…”
Section: The Use Of Ict In General Practicementioning
confidence: 99%
“…At first glance these may appear to be at odds with one another, clinical aiming at quality and efficiency of medical care and business aiming towards profitability and budgetary concerns. However, recent studies (Bonneville & Pare 2006, Lievens & Jordanova 2004 suggest that for any medical or healthcare function to be truly viable there must be equality between medical and business efficiency. Indeed, Kuruvilla et al (2004) suggest that the use of ICT in general practice not only centralise geographically dispersed resources, thus promoting flexibility and economies of scale, but they promote efficiency, enhance quality of care and encourage partnerships both between practitioners as well as between patients and practitioners.…”
Section: The Nature Of Ict In Medical Practicementioning
confidence: 99%